Sosialisasi Digital Marketing pada UKM di Desa Mangunegaran, Kecamatan Mrebet, Kabupaten Purbalingga. - Dewi Susilowati; Rini Widianingsih; Widyahayu Warmmeswara Kusumastati; Siti Maghfiroh; Bambang Setyo Budi Irianto (Jurnal Pengabdian Bisnis dan Akuntansi, 2025)
Mangunegaran Village in Mrebet District, Purbalingga Regency, is home to many Micro, Small, and Medium Enterprises (MSMEs), particularly in the traditional food and bamboo handicraft sectors. However, the utilization of digital marketing among local MSME actors remains low. This community service activity aimed to improve MSME actors’ understanding of digital marketing through basic outreach and training. The methods used included needs identification, material preparation, outreach activities, and a simple evaluation using pre-test and post-test. The results showed an increase in participants’ understanding of the importance of digital branding, simple content creation, and the use of social media for promotion. This outreach is expected to serve as an initial step for MSMEs in Mangunegaran to expand their market through digital channels.